Screening and identification of horticultural soil fungi for their evaluation against the plant parasitic nematode Nacobbus aberrans - Sosa, Ana Laura (2018)
The plant-parasitic nematode Nacobbus aberrans is an endoparasite causing severe losses to a wide range of crops from North to South America. The use of native antagonistics fungi may be considered as a posible biological control alternative to reduce the damages caused by this species. Antagonistics effects of 66 potential nematophagus fungi against eggs (J1) and second ?stage juveniles J2 of N.aberrans, were evaluated in vitro on wáter agar. DGC test sowed significant differences (p<0.0001) in the efficacy of some fungal isolates tested, with parasitisms levels for J1 and J2 of 0-95 and 1-78 % respetively. Five isolates of Purpureocillus lilacinum , Metarhizium robertsii and Plectosphaerella pluvivora appeared as the most effective antagonist of N. aberrans, relying on hyphae and adhesive conidia in host infection proces.